Influence of high-density lipoprotein cholesterol on coronary collateral formation in a population with significant coronary artery disease - Hsu, Po-Chao (BioMed Central, 2013)
BACKGROUND: Coronary collateral circulation plays an important role in protecting myocardium from ischemia and reducing cardiovascular events. Low High-density lipoprotein cholesterol (HDL-C) level is a strong risk factor for coronary artery disease (CAD) and is associated with poor cardiovascular outcome. It was recently reported to be associated with poor coronary collateral development in Turkish population. Hence, we investigated the influence of HDL-C on coronary collateral formation in Chinese population. METHODS: We evaluated 970 consecutive patients undergoing coronary angiography, and 501 patients with significant coronary artery disease (SCAD) were finally analyzed. The collateral scoring system developed by Rentrop was used to classify patient groups as those with poor or good collaterals. RESULTS: The patients with poor collaterals had fewer diseased vessels (1.97 ± 0.84 vs 2.47 ± 0.68, p < 0.001) and lower diffuse score (2.65 ± 1.63 vs 3.76 ± 1.78, p < 0.001). There was no significant difference in HDL-C and other variables between good and poor collaterals. Multivariate analysis showed only number of diseased vessels (odd ratio 0.411, p < 0.001) was a significant predictor of poor collateral development. CONCLUSIONS: The extent of CAD severity but not HDL-C level was the most powerful predictor of coronary collateral formation in our Chinese population with SCAD.